From Revolutionaries to Citizens: Antimilitarism in France, 1870-1914 - Davis, Lawrence H. (Labour / Le Travail, 2004)
The article reviews the book, "From Revolutionaries to Citizens: Antimilitarism in France, 1870-1914," by Paul B. Miller.